EFFECT OF FORCE MOLTING USING HIGH LEVELS OF DIETARY NANO ZINC OXIDE ON PRODUCTIVE PERFORMANCE OF LAYING HENS - Al-Mosawy, H.A.; Al-Hassani, D.H (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The experiment was conducted during 1/4/2020-7/31/2020 to study the effect of adding high levels of nano-zinc oxide with the diet to induce force molting in laying hens by measuring some productivite traits. Eighty laying hens, 69 weeks old were used, randomly divided into four treatments, five replicates for each treatment using CRD. Experimental treatments were: first treatment (T1), second treatment (T2), third treatment (T3) and fourth treatment (T4), which means control treatment without molting, adding 10, 15, and 20 gm of nano-zinc oxide / kg feed respectively. Results showed significant decreases (P<0.01) in egg production and almost ceased in the 2nd and 3rd week after start molting. Egg production increased significantly in T2, T3, and T4 when compared to T1 since 2nd week of starting egg production until the end of the period. The mean of egg production was 54.8, 75.19, 74.9 and 78.0 in T1, T2, T3 and T4 respectively . There was a significant decreases in body weight during the molting and most of the loss was in liver, pancreas, ovary and oviduct. It can be concluded that 10, 15 and 20 gm of nano-zinc oxide/kg feed showed high efficiency in inducing molting and producing eggs, and the level of 20 gm was the best.